السعادة النفسية وعلاقتها ببعض المتغيرات لدى الإعلاميين (بحث ميداني) - جرجيس, مؤيد اسماعيل; رؤوف, تاڤان فرهاد (Sulaimani Journal for Humanities, 2022)
The current research aims at identifying the level of significance of differences in psychological happiness among journalists, according to the variables (gender, governorate, age, length of service in the media, and type of media work). (452) journalists were selected as the research sample from the city of Erbil and Sulaymaniyah for the academic year (2020-2021). For this study, the researchers relied on the Oxford Happiness List Scale, authored by (Argyle & Lu, 1995) and the scale of (Ryff, 1989; Rosemary, 2006) for preparing the psychological happiness scale. Face validity, psychometric properties and the translation validity of the scale were verified. The result of the reliability by Cronbach’s alpha method was (0.95) and splite -half was (0.96). After the application, Statistical Package for Social Sciences (SPSS) was used to process the research data. The results showed that the level of psychological happiness among the journalists is spread among the sample members at a rate of (%91.814), and there are no statistically significant psychological happiness differences according to gender among the journalists. However, there are statistically significant psychological happiness differences according to the governorate in favor of the journalists in Erbil governorate. No differences were detected in psychological happiness according to the length of service in the media and the type of media work among the journalists, but there are statistically significant psychological happiness differences according to the age of the journalists in favor of the age group (19-23) in comparison to the other groups.
Keywords: Psychological Happiness; gendar; governorate; age; lengh of sevice in the media; type of media work